2016
DOI: 10.1177/0899764015603204
|View full text |Cite
|
Sign up to set email alerts
|

Modern Portfolio Theory and Nonprofit Arts Organizations

Abstract: This study examines the revenue structures of nonprofit organizations in the arts subsector to identify theoretically ideal revenue portfolios by examining the risk, return, and covariance of revenue streams. This article examines four major sources of revenue for arts organizations and builds on Kingma's work on nonprofit revenue portfolios by carrying out the theoretical modeling suggested in his seminal work. Beyond identifying the efficient frontier, this approach can also reveal the composition of theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 28 publications
0
26
0
1
Order By: Relevance
“…On the one hand, the dataset represents the population of nonprofits that were required to report to the IRS between 1998 and 2003, and provides comprehensive financial information that allows examination of detailed revenue categories. It has been regarded as “the most nuanced or comprehensive dataset available” (Chang, Tuckman, & Chikoto‐Schultz, , p. 25), and served other recent studies on revenue diversification (Chikoto et al, ; Grasse et al, ; Qu, 2016). On the other hand, it includes a short and representative time period, which covers both the economic growth in the late 1990s and the recession in the early 2000s.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the one hand, the dataset represents the population of nonprofits that were required to report to the IRS between 1998 and 2003, and provides comprehensive financial information that allows examination of detailed revenue categories. It has been regarded as “the most nuanced or comprehensive dataset available” (Chang, Tuckman, & Chikoto‐Schultz, , p. 25), and served other recent studies on revenue diversification (Chikoto et al, ; Grasse et al, ; Qu, 2016). On the other hand, it includes a short and representative time period, which covers both the economic growth in the late 1990s and the recession in the early 2000s.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have instead focused on what is an optimal combination of revenue sources, applying insights from MPT. In particular, recent studies have shown that lower revenue concentration as indicated by lower levels of HHI do not always correspond with optimal portfolios (Grasse et al, 2016;Qu, 2016). Extending the literature, this study examines the empirical relationship between the revenue diversification index based on HHI and the portfolio risk measure based on MPT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations